Comparison of a bottom-up and a top-down approach for the creation of contact openings in a multi-stack oxide layer at the front interface of Cu(In, Ga)Se2. (1st May 2022) - Buldu, Dilara G.; de Wild, Jessica; Kohl, Thierry; Birant, Gizem; Brammertz, Guy; Meuris, Marc; Poortmans, Jef; Vermang, Bart
Highlights: A multi-stack oxide layer (Al2 O3 /HfO2 ) is applied at the front interface of CIGS. A multi-stack design is used to prevent unwanted etching of Al2 O3 during the CBD. A bottom-up (BU) and a top-down (TD) approach is used to create contact openings. A NaCl template patterning was used to create a pattern on the CIGS or AlOx surface. The TD approach shows more promising results for the front interface applications. Abstract: The implementation of an oxide layer with contact openings to the Cu(In, Ga)Se2 (CIGS) interfaces has become especially popular to reduce the recombination losses, resulting in a higher open-circuit voltage. While implementing this approach on the back surface is straightforward, it is more complicated for the front surface due to the roughness of the absorber as well as material selection constraints imposed by further processing steps. In this contribution, an AlOx /HfOx multi-stack oxide layer with contact openings is applied between the CIGS and CdS layers. Two different approaches to create contact openings in multi-stack oxide layer are presented, and their advantages and disadvantages are investigated. In the bottom-up approach (BU), a NaCl salt pattern is created on the CIGS absorber surface, while in the top-down approach (TD), the pattern is created on the AlOx layer surface. Time-resolved photoluminescence (TR-PL) shows that the multi-stack design improves the PL decay time regardless of the approach, but when the CdS layer is deposited, the PL decay time decreases. A more severe decrease is observed in case of the BU approach. Capacitance-Voltage measurements show that there is no impact on doping level when the NaCl pattern is created on an AlOx surface. This work shows that any oxide material, even if not chemically resistant to the chemical bath deposition, can be applied at the CIGS/buffer layer interface, and additionally, any template can be used to create contact openings while preventing interaction between the material used for patterning and the CIGS, using the TD approach.